Job Commitment among Agriculture Development Officers and Horticulture Development Officers of Punjab - Varinder Singh and Prabhjot Kaur, (Indian Journal of Extension Education, 2015)
The present study is conducted to know the job commitment among agriculture district officers (ADO) & horticulture district officers (HDO) of state department of agriculture and horticulture department of Punjab state. 120 ADOs and HDOs was selected by using probability proportion to their numbers. It was found that majority of HDOs and ADOs have medium level of commitment toward their job age and service experience of the respondents were found positively and significantly associated with their job commitment.